J.W. Phelps correspondence and journal entries - Phelps, J. W. (John Wolcott), 1813-1885.
Correspondence and journal entry fragments relating primarily to Phelps's experience as a U.S. Army officer in Florida during the Second Seminole War, 1835-1842. The letters are addressed chiefly to Phelps's sister, Helen M. Phelps, and contain observations on Creek and Seminole Indian traditions; military life, strategy, and leaders; and descriptions of Florida's plant and animal life.
U.S. Army officer and abolitionist.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Phelps, Helen M. -- Correspondence; United States. -- Army -- Military life; United States. -- Army -- Officers; Animals -- Florida; Command of troops -- History -- 19th century; Creek Indians -- Social life and customs; Indians of North America -- Social life and customs; Indians of North America -- Wars -- 1815-1875.; Military art and science -- United States -- History -- 19th century; Plants -- Florida; Seminole Indians -- Social life and customs; Seminole War, 2nd, 1835-1842.; Strategy; Abolitionists; Army officers